Dynamic Modeling of Three-Phase Asymmetric Power Transformers with Magnetic Hysteresis: No-Load and Inrush Conditions - Moses, Paul; Masoum, Mohammad Sherkat; Toliyat, H. (IEEE Power Engineering Society, 2010)
A new dynamic model of a three-phase three-leg transformer for steady-state and transient operating conditions is proposed in this paper. With very few exceptions, the existing models oversimplify the magnetic interactions in multileg core topologies and employ single-value nonlinear functions for modeling core nonlinearities. Unfortunately, this does not provide sufficient accuracy for a wide range of dynamic disturbances such as dc bias, ferroresonance, and inrush. For this purpose, a new time-domain model based on magnetic-circuit theory is developed to include dynamic-hysteresis behavior (major and minor loops) in asymmetric three-leg core topologies. Furthermore, a new analysis is performed to study the impacts of hysteresis on no-load and transient inrush current behavior in three-phase transformers. Simulation results have been successfully compared with measurements to verify the accuracy of the proposed model.